Improving Children's Fine Motor Skills Through Paper Quilling Activities at TK S IT Cendekia Takengon - Shaulita, Rizkia; Suminah, Suminah; Cibro, Juniara Fitri (Lembaga Riset Mutiara Akbar, 2025)
Fine motor skills are an important aspect in early childhood development that needs to be optimally stimulated. This study aims to improve children's fine motor skills through paper quilling activities at the IT Cendekia Takengon Private Kindergarten. The study used a Classroom Action Research (CAR) approach with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 20 children, consisting of 10 boys and 10 girls. Data collection techniques were carried out through observation and documentation, while data analysis used percentage formulas and qualitative descriptions. The results of the study showed a significant increase in children's fine motor skills. In the pre-action, the percentage of achievement was only 45%. After the intervention in cycle I, it increased to 64%, and in cycle II it reached 83%. This increase reflects that paper quilling activities are effective in training hand-eye coordination, paper rolling, cutting, and sticking skills, as well as children's ability to express creativity through artwork. Thus, paper quilling activities can be used as an alternative learning strategy to develop fine motor skills in early childhood in a fun and meaningful way.